2018
DOI: 10.1016/j.pupt.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopolysaccharide on the responsiveness of equine bronchial tissue

Abstract: Recurrent airway obstruction (RAO) is a main characteristic of horses with severe equine asthma syndrome. The presence of bacterial lipopolysaccharide (LPS) in the airways of horses is thought to play a crucial role in the clinical expression of this disorder. This study pharmacologically characterized the effect of LPS on the responsiveness of equine bronchial tissue. Equine isolated bronchi were incubated overnight with LPS (0.1-100 ng/ml) and then stimulated by electrical field stimulation (EFS). The role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…The present study demonstrated that TRPV1 was present as mRNA and protein in the equine synovial membrane in healthy and diseased joints. These results are consistent with previous studies, where TRPV1 has been found in synovial tissue from several other species [26][27][28], and in both neural and respiratory tissue in the horse [45].…”
Section: Discussionsupporting
confidence: 94%
“…The present study demonstrated that TRPV1 was present as mRNA and protein in the equine synovial membrane in healthy and diseased joints. These results are consistent with previous studies, where TRPV1 has been found in synovial tissue from several other species [26][27][28], and in both neural and respiratory tissue in the horse [45].…”
Section: Discussionsupporting
confidence: 94%
“…The ex vivo study by Calzetta et al, 2018 confirms and extends the previous results by Venugopal et al, 2009 and suggests that the environmental exposure to bacterial of lipopolysaccharides may represent a crucial factor in modulating the bronchial responsiveness of severe equine asthma [ 20 , 23 ]. A chronic exposure to high concentration of inhaled endotoxin in fact has a deleterious effect in equine distal airways: it triggers dysfunctional airway smooth muscle (ASM) contractility due to the stimulation of capsaicin-sensitive sensory nerves, increased the release of NKA and the activation of NK2 receptors.…”
Section: Discussionsupporting
confidence: 68%
“…However, little information exists regarding the involvement of NKA receptors in the horse, moreover limited to the intestine [ 50 ] and to the lung of horses affected by EA [ 20 ]. Recently, the receptors of the capsaicin sensitive-sensory nerves stimulated by bacterial of lipopolysaccharides, capable of inducing neurogenic inflammation [ 23 ] as occur in human airways [ 48 ] have been investigated in equine bronchial tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change in R L ≥1 cm H 2 O/L/s may also help clinicians to identify whether individual asthmatic horses could be clinically responsive to a long‐acting β 2 ‐agonist (LABA) instead of a long‐acting muscarinic antagonist (LAMA), and vice versa, when the agents are administered in monotherapy as rescue medication in subjects with acute airway hyper responsiveness, or whether adding a second bronchodilator agent may clinically improve lung function . The MID based on change in R L might guide the choice of maintenance therapy .…”
Section: Discussionmentioning
confidence: 99%